A study on Chinese culture learning among non-Chinese students in Malaysia - Ju, Meng; Wang, Yuexin; Yong, Ying Mei (2016)
Learning Chinese became popular in the global. Chinese culture also become important in Chinese learning. Chinese culture course included teaching language and culture. It was increase the social ability for second language learners. However, Malaysia non-Chinese undergraduate were miss understand some Chinese culture meaning due to they were did not really understand the Chinese culture. Thus this study investigated the Chinese culture learning among non-Chinese students in Universiti Malaysia Pahang. A total of 60 non-Chinese undergraduate were given pre-test and post-test before and after the Chinese culture course. The finding showed a significant improvement among undergraduates and master the vocabulary in Chinese culture. This article may inspirit the Chinese teachers in teaching Chinese culture and enhance their teaching in Chinese culture.